Hetero Agglomeration Processes in a High‐Gradient Magnetic Filter Design. Issue 3 (20th January 2016) - Förster, Eva; Schmidt, Armin; Rhein, Frank; Anlauf, Harald; Nirschl, Hermann
Abstract: An innovative magnetic filter in combination with a Mandhala magnet for oil filtration processes has been developed. With this filter design also nonmagnetizable particles can be separated. Responsible are hetero agglomeration processes that arise due to agglomeration of magnetizable with nonmagnetizable particles. Separation efficiencies in dependence of the particle size distribution and particle shape are quantitatively determined. An evaluation method for the quantification of the separation efficiency of nonmagnetizable particles is developed and validated by experimental data. On this basis, a statement about the efficiency of the hetero agglomeration can finally be made. Abstract : High gradient magnetic separation is a reliable method to separate para‐ and ferromagnetic particles from gear oils. Using the developed evaluation procedure, the successful separation of diamagnetic particles from a hydraulic oil suspension is proven and quantitatively determined. The proposed filter design also allows the separation of nonmagnetizable particles.